Patterns of Hamstring Muscle Tears in the General Population: A Systematic Review. - Barbara Kuske; David F Hamilton; Sam B Pattle; A Hamish R W Simpson (PLoS ONE)
Background Hamstring tears are well recognised in the sporting population. Little is known about these injuries in the general population. Purpose Evaluating the rates, patterns and risk factors of non-sporting hamstring tears, compared to sporting related hamstring tears. Data sources MEDLINE, EMBASE, CINAHL, and the Cochrane Central Register of Controlled Trials (1989-2015). Study selection Studies reporting patients with a grade 2 or 3 hamstring muscle tear, identified clinically, confirmed by MRI imaging or direct visualisation during surgical exploration. Data synthesis 144 sets of linked data were extracted for analysis. Most injuries were in males (81.3%), where mean age at injury was lower (30.2, 95% CI 29.1-31.3) than in females (35.4, 95% CI 32.4-38.4) p = 0.06. Key differences were found in the proportion of non-sporting injuries in patients under and over the age 40 (p = 0.001). The proportion of non-sporting injuries was significantly higher in females compared to males (25.9% female non-sporting injuries, versus 8.5% male; p = 0.02). Avulsions were more frequently reported in non-sporting activities (70.5%). The proportion of such injuries was notably higher in females, though this failed to meet significance (p = 0.124). Grouped by age category a bimodal distribution was noted, with the proportion of avulsions greater in younger (age <15) and older patients (age > 40) (p = 0.008). 86.8% of patients returned to pre-injury activity levels with a similar frequency across all study variables; age, activity (sporting vs non-sporting) and injury type (avulsion vs tear). Conclusion This review highlights a proportion of adults suffering grade 2 or 3 hamstring injuries from activities other than the classic sports trauma. The majority of these non-sporting injuries were avulsion injuries that clustered in older female and skeletally immature patients suggesting a potential link to bone mineral density.